Violência física e fatores associados em participantes da pesquisa nacional de saúde do escolar (PENSE) - Romeiro, Juliana Souza (2019)
Introduction: Adolescence is a complex stage of the evolutive cycle, when individual, relational, community, and social factors can influence on development of violence. Objective: Investigate physical violence behavior on students in Brazilians schools and factors related. Material and Method: Secctional review using data from the National Survey of School Health (PeNSE) 2015, with students from the 9th grade. The outcome was the report of physical fighting involvement on 12 months and the exposure variables were related to socioeconomic and demographic conditions, unsecure surroundings, individual behavior, mental health, supervision and family support. For the data analysis, the multivariate logistic regression was used with a hierarchical approach. Results: The prevalence of involvement in the fight was 23.3%, greater in boys 30.2% (IC 29.3 – 31.0) and 16.7% (IC 16.0 – 17.4) in girls. The probability of get into a fight was increased by family agression OR 2.59 (2.31-2.90), alcohol consumption OR 2.49 (2.23-2.78), insecurity at school OR 1.68 (1.41-2.00), illicit drugs OR 1.55 (1.26-1.90), private school OR 1.52 (1.35-1.72), tobacco smoke OR 1.43 (1.16-1.72), sedentary lifestyle OR 1.35 (1.24-1.48), classes missing OR 1.31 (1.18-1.46), sleeplessness OR 1.27 (1.15-1.35), insecurity on the home-school path OR 1.24 (1.07-1.43) and loneliness OR (1.04-1.22). Probability of get into a fight decreased when the perception of being receiving support from parents and studying in private school OR 0.78 (0.69-0.89). Conclusion: Contributed to violence the family aggression, community and at school insecurity, drugs consumption behavior, classes missing and mental health impairment. Reduced the chances of violence be working on boys and for girls their parents support and be in private school.